2009
DOI: 10.1007/s10560-009-0190-0
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Studies of Child Welfare Training Effectiveness: Methods and Outcomes

Abstract: Although public child welfare agencies, as well as contracted private providers, conduct extensive amounts of training, the evaluation evidence for effectiveness of training interventions is sparse. This article provides a critical review of published reports of the child welfare training evaluation literature. When we conducted a search of the literature published since 1990, 14 articles met the criteria for inclusion. These articles are reviewed according to: training audience, training duration, research de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…In common with observations from others' reviews of studies of training in child protection in general (Carter et al, 2006, Collins et al, 2010 it is as if training the workforce is a forgotten component in child protection research, theorizing, and policy initiatives. While the evidence provided in this review is not sufficient for us to wholeheartedly recommend use of simulation, it does warrant further development and study.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…In common with observations from others' reviews of studies of training in child protection in general (Carter et al, 2006, Collins et al, 2010 it is as if training the workforce is a forgotten component in child protection research, theorizing, and policy initiatives. While the evidence provided in this review is not sufficient for us to wholeheartedly recommend use of simulation, it does warrant further development and study.…”
Section: Resultsmentioning
confidence: 74%
“…And yet there is a paucity of rigorous studies that contribute to an evidence base for educational and continuing training interventions and programs (Carter et al, 2006;Collins et al, 2010). A crucial component of ensuring child safety is child protection workers' competence in working with high-risk families.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of particular concern is the degree of empirical support for training effectiveness in evaluation studies. Collins et al (2010) found only 14 studies of empirically based child welfare training evaluation in their literature review of articles published in peer-reviewed journals since 1990. Antle et al (2008) advanced a model for child welfare training evaluation in 2008, but as yet little research has emerged in follow-up studies.…”
Section: Introductionmentioning
confidence: 99%